Earning Management dan Expected Future Earning di Bursa Efek Indonesia - Taofiq Rachmat; Hermanto Siregar; Tb Nur Ahmad Maulana (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2017)
The purpose of this study was to applicated M-score to identify earning management in Indonesian corporation. This study also aims to analyst future earning condition from kind of group or sector of corporation which is indicated doing earning management. This study took a sample of 42 corporation using criteria about corporation which is had negatif information. The results of multiple linear regression analysis show that there is evidence that companies with an Earning Management detected earn lower future earnings (a study in Indonesian Stock Exchange Market), the ability of forecast changes in future earnings stems from its ability of predictive power of M-Score (Earning Management Detection Model). There is also, evidence that group companies which had “high attention” from Regulator earn lower expected future earnings. Based on the results of this study, the stake holder are advised to consider M-score to make judgement about financial reports.Keywords: earning management, expected future earning, indonesian stock exchange market, m-score, cross- sectional time-series dataAbstrak: Tujuan dari penelitian ini adalah untuk mengkaji aplikasi M-Score untuk mengidentifikasi earning management pada korporasi di Indonesia. Penelitian ini juga bertujuan mengkaji kondisi expected future earning dari kelompok korporasi yang di informasikan terindikasi melakukan earning management. Penelitian ini mengambil sampel dari 42 korporasi dengan menggunakan kriteria korporasi yang memiliki informasi negatif. Hasil analisis regresi linier berganda menunjukkan terdapat bukti apabila korporasi yang terdeteksi earning management akan mendapatkan expected future earning yang rendah. Kemampuan memprediksi perubahan pada expected future earning didapat dari kemampuan prediksi yang kuat dari M-score (Model untuk mendeteksi adanya earning management). Penelitian menunjukkan bahwa ditemukan konglomerasi usaha yang mendapat pengawasan dari regulator mendapatkan expected future earning yang rendah. Berdasarkan hasil penelitian ini, pemangku kepentingan disarankan menggunakan M-score ketika melakukan penilaian pada laporan keuangan.Kata kunci: earning management, expected future earning, bursa efek indonesia, m-score, data panel